The world economy in 1999-2007: Bubble, bubble toil and trouble - Vos, Rob (Oxford University Press, 2018)
Between 1999 and 2007, global economic trends were characterized by the aftermath of the Asian financial crisis, the bubble and burst of the dot-com crisis, and a global recovery which triggered a boom in commodity prices and inflated housing and stock market bubbles in the US and other high-income countries. These trends culminated into the global financial crisis of 2008–9. Few observers saw this crisis coming. UN economists did. This chapter looks at what UN economists saw as risks, but other observers failed to see: (a) the widening savings–investment imbalances across countries; (b) the risks of cheap money in the context of unregulated finance; (c) the decoupling of economic growth between developed and developing countries; and (d) the risk of imminent exchange rate instability. Revisiting the history of this period is relevant for drawing lessons for the understanding of today’s buildup of another dot-com bubble and its possible consequences.